2008
DOI: 10.1519/jsc.0b013e31816a8440
|View full text |Cite
|
Sign up to set email alerts
|

Relative Importance of Strength, Power, and Anthropometric Measures to Jump Performance of Elite Volleyball Players

Abstract: The purpose of this investigation was to examine the potential strength, power, and anthropometric contributors to vertical jump performances that are considered specific to volleyball success: the spike jump (SPJ) and counter-movement vertical jump (CMVJ). To assess the relationship among strength, power, and anthropometric variables with CMVJ and SPJ, a correlation and regression analysis was performed. In addition, a comparison of strength, power, and anthropometric differences between the seven best subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
140
1
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(185 citation statements)
references
References 13 publications
9
140
1
9
Order By: Relevance
“…The inclusion of peak power at the knee and ankle joints in the overall regression model supports previous claims that CMJ performance is positively associated with lower-limb power (Ashley & Weiss, 1994;Nuzzo et al, 2008;Sheppard et al, 2008;Vanezis & Lees, 2005). The work-energy-power relationship makes it inevitable that greater joint powers result in more positive work done and so greater total body kinetic energy and mass centre vertical velocities at take-off.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The inclusion of peak power at the knee and ankle joints in the overall regression model supports previous claims that CMJ performance is positively associated with lower-limb power (Ashley & Weiss, 1994;Nuzzo et al, 2008;Sheppard et al, 2008;Vanezis & Lees, 2005). The work-energy-power relationship makes it inevitable that greater joint powers result in more positive work done and so greater total body kinetic energy and mass centre vertical velocities at take-off.…”
Section: Discussionsupporting
confidence: 76%
“…As an indicator of maximal capabilities of the knee extensor musculature, a greater peak isometric knee extension torque enables greater joint torques and powers to be produced during the CMJ. However, whilst the inclusion of peak isometric torque in the isometric regression furthers the existing evidence for a relationship between strength and CMJ height (Ashley & Weiss, 1994;Sheppard et al, 2008;Wisløff et al, 2004), CMJ peak knee power explained a much greater proportion of the performance variation (44% versus 18%). Similarly, Young, Wilson, and Byrne (1999) showed that CMJ height is more closely related to measures of speedstrength qualities than maximum strength.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Bu araştırmada özellikle yavaş ip atlayan grupta arka arkaya yapılan derin sıçramalarda, diz ekleminin, uzun süre fleksiyonda kalması ve sabit hızda çalışmasının dikey güç üzerinde etkili olmadığını söylemek mümkündür. Bununla birlikte bazı çalışmalar kuvvet ölçümleri ve dikey güç arasında güçlü bir ilişki olduğunu; güç ve kuvvet kalitesinin belli bir dereceye kadar dikey sıçrama performansını olumlu yönde etkilediğini düşündürmektedir [21,22]. Dolayısıyla uzama-kısalma döngüsü frekansı, antrenman süresi, sahip olunan kuvvet miktarı ve sıçrama …”
Section: Wingate Testiunclassified
“…Volleyball has become a very popular sport played in many countries worldwide (Aouadi et al, 2012;Sheppard et al, 2008;Sheppard et al, 2011). Throughout the history of volleyball the rules have been modified to make it a more exciting spectator sport (Ureña, Gallardo, Delgado, Hernández, & Calvo, 2000).…”
Section: Introductionmentioning
confidence: 99%